The Formation of Personality in the Course of Socialization - Ostapiovskyi, Oleksandr (Psychological Prospects Journal, 2014)
Economic socialization as social and psychological process of individual adaptation to economic system of society is highlighted in the article. The person in modern society is under constant impact of increasing competition, which contributes to his/her social and economic relations. The individual development of personality greatly depends on economic consciousness. The psychological and economic characteristics of personality develop during period of economic socialization. The ultimate goal of economic socialization is development of personality as the subject of economic activity. The author reveals the main factors of economic socialization: system of society values, complex of individual needs and motives, individual mental representations of values, social criteria (age, social status and role, gender). The problem of economic socialization is relatively new one; it has been represented in native psychology since 2000. The author distinguishes three approaches to study of economic socialization: informational, psychological, and behavioral. The structural components (cognitive, affective, and conative) and forms of economic socialization (goal directed, spontaneous, and self-directed), kinds of economic socialization (working, consumer, economic, voluntary, and forced), criteria and factors (complex of different values) were analyzed. Subjective experience, world representation and mental codes of economic consciousness are treated as the main determinants of individual attitude towards economic situations and phenomena.